LANGUAGE STYLE ANALYSIS IN THE LYRICS OF THE SONG CAK CULAY NABUY-NABUY BY MUHAMMAD YUSUF (STILISTIC STUDY) - Habibansyah, Afeby Ade (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
This study aims to identify, analyze and reveal the meaning of language style in the lyrics of the song "Cak Culay Nabuy Nabuy" by Muhammad Yusuf using a stylistic approach. The research data used by the author are the lyrics of the song Cak Culay Nabuy Nabuy" by Muhammad Yusuf. The main focus of this study is to analyze the style of language which includes metaphor, hyperbole, symbolism, repetition, pleonasm, tautology, climax, irony, cynicism and satire. The research method used is descriptive qualitative with a case study design, where data is collected through documentation techniques and analyzed using note-taking and content analysis techniques. The results of this study indicate that there are 3 findings of language style and 8 language styles in the song lyrics that are found including: 1) comparative language style with metaphor, hyperbole and symbolic language styles, 2) affirmative language style with repetition and pleonasm, 3) satirical language style with irony, cynicism and satire. The findings consist of comparative language style found 3 findings equivalent to 37.5%, affirmative language style 2 findings equivalent to 25%, satirical language style 3 findings equivalent to 37.5%.